Party politics in India : the development of a multi-party system. - Weiner, Myron (Princeton legacy library., 1957)
A major study of India's developing party system. The author, who spent 18 months in India, employs a series of party case studies to assess India's chances at building a stable political framework. Originally published in 1957. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.